Effectiveness of learning videos on language skills in learning Indonesia - Evi Sofia; Cepi Riyana (Inovasi Kurikulum)
Oral language skills are important in basic education, especially in learning Indonesia. Interactive learning, such as learning videos, educational applications, and interactive simulations, are expected to increase student engagement and facilitate mastery of language skills. This research examines the effectiveness of using learning videos in improving students' language skills in Indonesia. The research method used is a quantitative method with a quasi-experiment design. The research subjects were 63 grade V elementary school students in one of the schools in Bandung Regency. This research was divided into two groups consisting of 33 class Va students as the experimental group who used learning videos and 30 class Vb students as the control group who did not use learning videos. The data was collected through language skills tests before and after treatment, observation sheets, and student response questionnaires. The research showed that students who studied using instructional videos significantly improved their language skills compared to those without this media. These findings indicate that learning videos can be an effective alternative media for improving students' language skills in elementary schools.